Water Abundance of Dunes in Gale Crater, Mars From Active Neutron Experiments and Implications for Amorphous Phases - T. S. J. Gabriel; C. Hardgrove; S. Czarnecki; E. B. Rampe; W. Rapin; C. N. Achilles; D. Sullivan; S. Nowicki; L. Thompson; M. Litvak; I. Mitrofanov; R. T. Downs (Geophysical Research Letters)
Abstract We report the water abundance of Bagnold Dune sand in Gale crater, Mars by analyzing active neutron experiments using the Dynamic Albedo of Neutrons instrument. We report a bulk water‐equivalent‐hydrogen abundance of 0.68 ± 0.15 wt%, which is similar to measurements several kilometers away and from those taken of the dune surface. Thus, the dune is likely dehydrated throughout. Furthermore, we use geochemical constraints, including bulk water content, to develop compositional models of the amorphous fraction for which little information is known. We find the amorphous fraction contains ∼26‐ to 64‐wt% basaltic glass and up to ∼24‐wt% rhyolitic glass, suggesting at least one volcanic source for the dune material. We also find a range of hydrated phases may be present in appreciable abundances, either from the incorporation of eroded aqueously altered sediments or the direct alteration of the dune sand.